Planning and operation of an energy Hub Model for Reducing Grid Electricity Dependency in a virtual Industrial Park (Development Engineering Conferences Center Articles Database, 2025)
Large industrial parks are major energy consumers whose heavy reliance on the national grid often leads to production losses and equipment damage during power outages, significantly impacting their financial performance. To address this critical issue, this study develops a linear Energy Hub (EH) model for the optimal planning and operation of an integrated energy system. The proposed linear framework ensures computational efficiency while effectively managing the multi-energy demands of the park and reducing its grid dependency. Simulation results demonstrate that this configuration increases electricity supply reliability by 1.01% and reduces maximum grid dependency by at least 20%. In addition, the model's economic robustness was tested through a sensitivity analysis on grid electricity costs, showing that a 15% price increase makes the internal generation assets of the hub more economically favorable, effectively minimizing grid usage. This enhanced autonomy directly mitigates the impact of grid blackouts, safeguarding industrial processes and protecting revenue streams.